A study in Augustine and Calvin of the Church regarded as the number of the elect and as the body of the baptized - Russell, S (1958)
﻿ Preface. For the greater part of the history of the Christian Church the doctrines of baptism and predestination have been uneasy bed-fellows. At times, the former has gained the predominance and the latter has been relegated to the region of philosophical prolegomena to faith, having no immediate connection with the Christian life. In other periods, the doctrine of predestination has gained the ascendency and the importance of baptism has been minimized. Nevertheless, both these aspects of the Christian faith are strikingly present in the New Testament, and in no way do we find there premonitions of the tensions between them in the later history of the Church. Is this because of the unsystematic nature of the New Testament faith which evaded these difficulties through its own lack of order, or is there a deeper reason for the primitive harmony between these two aspects of Christian theology? [contined in text ...]